(untitled) (Applied Biological Research, 2013)
The present study was aimed to assess alkaline protease production by a locally isolated soil fungus Scopulariopsis spp. The factors influencing enzyme production were optimized under submerged conditions. Maximum enzyme production occurred on 5th day of incubation on fermentation medium with initial pH 9.0, incubation temperature 37ºC, inoculum concentration 3%, casein 2% as substrate and 1.5% tryptone as nitrogen source. Under these optimized conditions, about 3-fold increase in protease activity (from 5.85 to 17.77 U ml-1) was noticed. High enzyme activity at alkaline pH suggested that the fungus can be exploited for use in leather processing and detergent industries.